(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
To give secure support to biometrics recognition this system deals with multimodal recognition (finger print + Iris recognition) to give efficient performance in the biometrics recognition. The kaggle & MRL eye database is used for the image for both finger print and Iris recognition, 225X225 image size taken into the system and feature extraction made namely edge and color then, combine both the feature together and stored into database. The same procedure applicable for training image as well as testing image. Haar transform, Fourier Transform and Laplace Transform for the feature extraction used and compare the result among the transform result justify the efficiency of the best transform. Now, The testing image load into the system feature extraction made and match with the database for the secure process in multi model biometrics.